Culturally Adapted Cognitive Behavioral Therapy Plus Problem Management (CA‐CBT+) With Afghan Refugees: A Randomized Controlled Pilot Study. Issue 6 (5th November 2020) - Kananian, Schahryar; Soltani, Yasaman; Hinton, Devon; Stangier, Ulrich
Abstract: Culturally adapted cognitive behavioral therapy (CA‐CBT) is a well‐evaluated, transdiagnostic group intervention for refugees that uses psychoeducation, meditation, and stretching exercises. In the current study, we added problem‐solving training to CA‐CBT and evaluated this treatment (i.e., CA‐CBT+) in a randomized controlled pilot trial with a sample of Farsi‐speaking refugees. Participants ( N = 24) were male refugees diagnosed with DSM‐5 PTSD, major depressive disorder, and anxiety disorders who were randomly assigned to either a treatment or waitlist control (WLC) condition. Treatment components were adapted both to the specific cultural background and the current social problems of asylum seekers. Assessments were performed pretreatment, 12‐weeks posttreatment, and 1‐year follow‐up. The primary treatment outcome was the General Health Questionnaire (GHQ‐28); secondary outcome measures included the Posttraumatic Stress Disorder Checklist, Patient Health Questionnaire, Somatic Symptom Scale, World Health Organization Quality of Life, and Emotion Regulation Scale. Eleven of 12 participants were randomized to CA‐CBT+ completed treatment. Based on intent‐to‐treat data, large between‐group effect sizes were seen at posttreatment in the GHQ‐28, d = 3.0, and for most secondary outcome measures. Improvements for individuals in the treatment group decreased at 1‐year follow‐up, but effect sizes demonstrated continued large improvements on all measures as compared to pretreatment levels. In summary, CA‐CBT+ led to large improvements in general psychopathological distress and quality of life, which were maintained in the long term. In addition, the dropout rate was very low, with delivery in group format. Thus, problem‐solving training appears to be a promising addition to CA‐CBT. Resumen: SpanishAbstractsby Asociación Chilena de Estrés Traumático (ACET) Terapia cognitivo‐conductual adaptada culturalmente más manejo de problemas (CA‐CBT+) con refugiados afganos: un estudio piloto controlado aleatorizado CA‐CBT+ CON REFUGIADOS AFGANOS La terapia cognitivo‐conductual adaptada culturalmente (CA‐CBT en su sigla en inglés) es una intervención grupal transdiagnóstica bien evaluada para refugiados, que utiliza psicoeducación, meditación y ejercicios de estiramiento. En el estudio actual, agregamos capacitación en resolución de problemas a CA‐CBT y evaluamos este tratamiento (es decir, CA‐CBT+) en un ensayo piloto controlado aleatorizado con una muestra de refugiados de habla farsi. Los participantes ( N = 24) eran varones refugiados diagnosticados con TEPT según DSM‐5, trastorno depresivo mayor y trastornos de ansiedad que fueron asignados al azar a un tratamiento o una condición de control en lista de espera (CLE). Los componentes del tratamiento se adaptaron tanto al contexto cultural específico como a los problemas sociales actuales de los solicitantes de asilo. Las evaluaciones se realizaron antes del tratamiento, 12 semanas después del tratamiento y un año de seguimiento. El resultado primario del tratamiento fue el Cuestionario de Salud General (GHQ‐28); los instrumentos de resultados secundarios incluyeron la lista de verificación del trastorno de estrés postraumático, el cuestionario de salud del paciente, la escala de síntomas somáticos, la calidad de vida de la Organización Mundial de la Salud y la escala de regulación de las emociones. Once de los doce participantes fueron asignados al azar al tratamiento completo con CA‐CBT+. Según los datos por intención a tratar, se observaron grandes tamaños de efecto entre los grupos en el postratamiento en el GHQ‐28, d = 3.0, y para la mayoría de las medidas de resultado secundarias. Las mejoras para los individuos en el grupo de tratamiento disminuyeron en el seguimiento de 1 año, pero los tamaños del efecto demostraron grandes mejoras continuas en todas las medidas en comparación con los niveles previos al tratamiento. En resumen, CA‐CBT+ produjo grandes mejoras en el malestar psicopatológico general y la calidad de vida, que se mantuvieron a largo plazo. Además, la tasa de deserción fue muy baja, con entrega en formato grupal. Por lo tanto, la capacitación en resolución de problemas parece ser una adición prometedora a CA‐CBT. 抽象: 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 JOTS‐20‐0097.R2 Kananian Culturally adapted CBT plus problem management (CA CBT+) with Afghan refugees: a randomized controlled pilot study Traditional Chinese 標題: 對阿富汗難民應用因應文化調節的CBT加困難管理(CA CBT+):隨機對照試驗研究 撮要: 因應文化調節的認知行為治療(CA‐CBT)是為難民而設, 廣受檢視、跨診斷的組別干預, 使用心理教育、正念和伸展運動。本研究在療法中加入一個解決困難訓練項目, 透過隨機對照試驗並以講波斯語的難民為樣本, 對這種療法(即CA‐CBT+)進行評估。樣本為確診患DSM‐5 PTSD、重性抑鬱疾患、焦慮症的男難民(N = 24)。他們被隨機分派到治療組或等候名單對照組(WLC)。我們因應尋求庇護人士的特殊文化背景和當前社會問題, 對治療元素作出調節。我們於樣本接受治療前, 及完成治療12週及1年後, 進行評估。一般健康問卷(GHQ‐28)用以檢視主要治療效果, 次級治療效果則以包括創傷後壓力症檢查表、病人健康問卷、身體症狀量表、世界衛生組織生活品質問卷、情緒調節量表等測量。12名樣本被隨機分派到接受CA‐CBT+, 當中11人完成治療。根據治療意向數據, GHQ‐28 (d = 3.0) 與大多數次級治療效果測量都顯示, 完成治療後, 組別間的效應量為大。治療組的樣本其症狀改善的幅度在一年後減小, 但效應量反映, 所有測量跟樣本接受治療前對比都持續有大幅改善。總括來說, CA‐CBT+在普遍心理疾病和生活品質方面都能帶來大幅改善, 這些改善長遠來說亦能維持。此外, 以組別方式提供治療, 中途退出治療率亦十分低。因此, 在CA‐CBT中加入解難訓練, 似乎能帶來益處。 Simplified Chinese 标题: 对阿富汗难民应用因应文化调节的CBT加困难管理(CA CBT+):随机对照试验研究 撮要: 因应文化调节的认知行为治疗(CA‐CBT)是为难民而设, 广受检视、跨诊断的组别干预, 使用心理教育、正念和伸展运动。本研究在疗法中加入一个解决困难训练项目, 透过随机对照试验并以讲波斯语的难民为样本, 对这种疗法(即CA‐CBT+)进行评估。样本为确诊患DSM‐5 PTSD、重性抑郁疾患、焦虑症的男难民(N = 24)。他们被随机分派到治疗组或等候名单对照组(WLC)。我们因应寻求庇护人士的特殊文化背景和当前社会问题, 对治疗元素作出调节。我们于样本接受治疗前, 及完成治疗12周及1年后, 进行评估。一般健康问卷(GHQ‐28)用以检视主要治疗效果, 次级治疗效果则以包括创伤后压力症检查表、病人健康问卷、身体症状量表、世界卫生组织生活质量问卷、情绪调节量表等测量。12名样本被随机分派到接受CA‐CBT+, 当中11人完成治疗。根据治疗意向数据, GHQ‐28 (d = 3.0) 与大多数次级治疗效果测量都显示, 完成治疗后, 组别间的效应量为大。治疗组的样本其症状改善的幅度在一年后减小, 但效应量反映, 所有测量跟样本接受治疗前对比都持续有大幅改善。总括来说, CA‐CBT+在普遍心理疾病和生活质量方面都能带来大幅改善, 这些改善长远来说亦能维持。此外, 以组别方式提供治疗, 中途退出治疗率亦十分低。因此, 在CA‐CBT中加入解难训练, 似乎能带来益处。